PENGARUH INTENSITAS MORAL DAN ETIKA PERSEPSIAN TERHADAP INTENSI KEPERILAKUAN TERKAIT SISTEM INFORMASI AKUNTANSI PADA PT. PUPUK ISKANDAR MUDA ACEH UTARA - Usman, Amru; Nufus, Hildayatun (Jurnal Akuntansi dan Keuangan, 2017)
This study aims to know the effect of moral intensity and perceived ethics on behavioral intentions related to accounting information system at PT. Pupuk Iskandar Muda, Aceh Utara. Sampling technique used census sampling where all the population used as the samples so that the samlpe in this study is 30. This study uses multiple linear regression analysis whit hypotesis testing using SPSS 16 for windows to analyze the data of this study. The results show that Moral intensity has a significant effect on behavioral intention relation to the accounting informasion system, Perceived ethical variables has a significant effect on behavioral intention related to information system.